The role of antioxidants and free radicals in the healing effects of Bacopa monniera on acetic acid-induced colitis in rats - Sharma, Himanshu; Chauhan, Saurabh; Singh, Punya Pratap; Goel, Raj K. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The aim to study and elucidate the healing effects of ethanolic extract of dried whole plant of Bacopa monniera against experimental colitis in rats. Methods: Bacopa monniera whole plant extract was administered orally, once daily for 14 days, to rats after induction of colitis with acetic acid. We studied its effects on: faecal output, food and water intake, and body weight changes and also examined colonic mucosal damage, inflammation and status of antioxidants: superoxide dismutase, reduced glutathione; free radicals: nitric oxide, lipid peroxidation on 15th day of the experiment. Antibacterial activity of the extract was also studied using in vitro procedures. Statistical comparison was performed using either unpaired ‘t’ test or one -way analysis of variance (ANOVA) and for multiple comparisons versus control group was done by Dunnett’s test. Results: Bacopa monniera whole plant extract decreased colonic mucosal damage, inflammation, faecal output and increased body weight in acetic acid induced colitis. It also showed antibacterial activity and enhanced the antioxidant but decreased free radicals. Acute toxicity study indicated no mortality or other ANS or CNS related adverse effects even with ten time effective dose indicating its safety. Conclusions: Bacopa monniera whole plant extract is safe, effective and could be beneficial as a complementary agent in treatment of ulcerative colitis.